Asthma exacerbations and eosinophilia in the UK Biobank: a genome-wide association study - Ahmed Edris; Kirsten Voorhies; Sharon M. Lutz; Carlos Iribarren; Ian Hall; Ann Chen Wu; Martin Tobin; Katherine Fawcett; Lies Lahousse (ERJ Open Research, 2024)
Background Asthma exacerbations reflect disease severity, affect morbidity and mortality, and may lead to declining lung function. Inflammatory endotypes (e.g. T2-high (eosinophilic)) may play a key role in asthma exacerbations. We aimed to assess whether genetic susceptibility underlies asthma exacerbation risk and additionally tested for an interaction between genetic variants and eosinophilia on exacerbation risk. Methods UK Biobank data were used to perform a genome-wide association study of individuals with asthma and at least one exacerbation compared to individuals with asthma and no history of exacerbations. Individuals with asthma were identified using self-reported data, hospitalisation data and general practitioner records. Exacerbations were identified as either asthma-related hospitalisation, general practitioner record of asthma exacerbation or an oral corticosteroid burst prescription. A logistic regression model adjusted for age, sex, smoking status and genetic ancestry via principal components was used to assess the association between genetic variants and asthma exacerbations. We sought replication for suggestive associations (p<5×10−6) in the GERA cohort. Results In the UK Biobank, we identified 11 604 cases and 37 890 controls. While no variants reached genome-wide significance (p<5×10−8) in the primary analysis, 116 signals were suggestively significant (p<5×10−6). In GERA, two single nucleotide polymorphisms (rs34643691 and rs149721630) replicated (p<0.05), representing signals near the NTRK3 and ABCA13 genes. Conclusions Our study has identified reproducible associations with asthma exacerbations in the UK Biobank and GERA cohorts. Confirmation of these findings in different asthma subphenotypes in diverse ancestries and functional investigation will be required to understand their mechanisms of action and potentially inform therapeutic development.